Research on Chinese Journalists' Scientific Literacy - Hu, Xiao Juan (Frontiers in Communication, 2022)
Journalists are always in the "second battlefield" of fighting against the epidemic. In the face of major public health events, their scientific literacy is directly related to the effect of emergency science popularization. This paper reviews the research on journalists' scientific literacy, clarifies the value of scientific literacy in journalism, and analyzes the cognition and practice of journalists’ scientific literacy, so as to explore feasible ways to effectively improve scientific literacy. The study found that journalists' scientific literacy has unique value in the crisis period. Journalists should improve scientific literacy from their own learning and professional training, while using new media technology to scientifically demonstrate information.